CASE LAW AS A PILLAR OF AN ADAPTIVE, TRANSPARENT, AND EFFECTIVE LEGAL SYSTEM IN INDONESIA: A LITERATURE REVIEW ON THE ROLE OF JUDICIAL DISCOVERY, DIGITALISATION OF JUDGMENTS, AND INTER-CASE CONSISTENCY - Gunawan Widjaja (Adisam Publisher, 2025)
This study discusses the role of jurisprudence as a fundamental pillar in building an adaptive, transparent, and effective legal system in Indonesia. Using a normative legal research method based on literature review, this study examines how judicial discovery functions as a mechanism for legal adaptation to social dynamics and substantive justice needs that are not always fulfilled by written regulations. In addition, this study explores the role of court decision digitisation in improving openness and access to information, which triggers accountability and public trust in judicial institutions. Consistency between cases is also analysed as an important element in upholding legal certainty and the effectiveness of the judicial system. The findings show that the synergy between judicial discovery, the digitisation of decisions, and consistency between cases can strengthen the existence of jurisprudence as a key pillar of Indonesia's modern legal system, which is responsive and reliable. The contribution of this research lies in strengthening the theoretical and practical foundations for the development of a more adaptive, open, and effective national legal system.